Attracting Foreign Direct Investment into Small and Medium Enterprises in the Southern Key Economic Region, Vietnam. - Duong Nguyen Duc; Anh Tran Tuan; Tu Bui Anh (International Journal of Small and Medium Enterprises and Business Sustainability, 2021)
The objective of this study is to propose solutions to increase the FDI attraction in the southern key economic region (SKER) in Vietnam in the future. This article uses the method of statistical analysis and comparison to assess the current situation of foreign direct investment (FDI) in the SKER in the period 2010-2018. The research results show the achievements of FDI attraction to the SKER and the problems encountered in practice. Through survey data and analysis of factors affecting regional linkages in FDI attraction, the article uses the exploratory factor analysis (EFA) method to evaluate the FDI attraction in SKER. The results show that there are 4 main factors including technical infrastructure, natural characteristics, preferential policies, and human resources that have a certain impact on the key economic region linkage to attract FDI to the SKER.